Hubungan antara External Locus of Control dengan Kepuasan Kerja pada Anggota Kepolisian - Rahmaini Fahmi; Jasmadi Jarmadi; Fatmawati Fatmawati (Psikoislamika: Jurnal Psikologi Islam, 2019)
Job satisfaction is one of the work variables that contribute greatly to the effectiveness of the organization and the work itself. Individual job satisfaction arises from a person's perception of how well the work provides something meaningful. On the other hand, external locus of control is a factor that influences an individual's perception of the environment, including the work environment. For this reason, this study aimed to find out how the relationship between external locus of control and job satisfaction is on Police Members at the Aceh Regional Police Headquarters. This study used a quantitative method with sampling based on simple random sampling technique. The sample in this study amounted to 287 people and the results showed that there was a relationship between external locus of control and job satisfaction on Members of the Police at the Aceh Regional Police Headquarters with Pearson correlation test values r=-0,232, p=0,000 (0,05). These results indicate that there is a very significant negative relationship between external locus of control and job satisfaction on Members of the Police at the Aceh Regional Police Headquarters.